Mother's Smart Card Effect on Mother's Knowledge and Awareness of Children's Fever in The Pre-Hospital Phase - Sapondra Wijaya; Wahyu Dwi Ari Wibowo; Abdul Rokhman; Firman Nugraha Putra; Huswatun Azmarina Yulandari; Encan Reazsari Anisya (Babali Nursing Research, 2022)
Introduction: Fever increases body temperature above 37.50 C, making the child uncomfortable; the child's body and face are hot, red, and shivers. Fever conditions also affect parents, especially mothers who will also feel anxious. This study aimed to determine the effect of the Mother's Smart Card on the knowledge and awareness of mothers in the management of children with fever in the pre-hospital phase. Methods: This study used a Quasi-Experimental design with a pre-test and post-test approach with a purposive sampling technique on 40 mothers. A mother's knowledge is measured by knowledge about fever. In contrast, vigilance is measured by how the mother behaves and her accuracy in making decisions when her child has a fever. All measurements used a questionnaire. Results: The results of data analysis using paired t-test showed a significant effect of the Mother's Smart Card on mother's knowledge and awareness in managing children with fever at home with a p-value of 0.000. Conclusion: This means that the Mother's Smart Card can increase the knowledge and awareness of mothers in the management of children with fever in the pre-hospital phase. This result is hoped that the Mother’s Smart Card can be a reference in increasing mothers' knowledge and awareness and minimizing treatment in inappropriate health facilities that can be at risk of transmitting other diseases.